KESADARAN HERMENEUTIK DALAM MEMBACA TEKS: MODEL IJTIHAD UMAR IBN AL-KHATTAB - Alma`arif Alma`arif (UIN Raden Mas Said Surakarta, 2016)
Umar ibn al-Khattab was one of the most controversial caliphs. He was a caliph that was courageous or